Design principles for photography - Webb, Jeremy (Routledge, 2020)
In an age over-saturated with photographic imagery, Design Principles for Photography demonstrates how design awareness can add a new level of depth to your images. By adapting and experimenting with the tried and tested techniques used by graphic designers every day, you can add dynamism and impact to your imagery, whatever the style or genre - something that today's editors, curators and publishers are all crying out for.